Improving Fundamental Movement Skills in Early Childhood through Outdoor Play Based on Gender - Andy Supriady; Agus Mahendra; Dian Budiana; Amung Ma’mun (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Basic movement skill (FMS) is an important factor that can influence physical activities. Playing outside can support a child overall health, learning process, and basic motor skill development. The purpose of this study was to determine early childhood motor development through outdoor play based on gender differences. This study used an experimental method with a one-group pretest-posttest design. The study population consisted of preschool children aged 5–6 years. The sample included 30 preschool children selected using purposive sampling, consisting of 12 boys and 18 girls. TGMD-2 test instrument was used to measure FMS. The results showed that there was no difference of the effect of the outdoor play program on the basic motor skills (FMS) of boys and girls. Locomotor skills and control objects indicates that there was a significant effect of the program intervention. It concludes that early motor skills of boys and girls were improved after participating in an outdoor play program. According to the result of this study, it is necessary to conduct a more detailed approach on gender differences, especially on their basic motor needs and participations in programmed outdoor activities to encourage the development of basic motor skills (FMS).